Strategy to Optimize the Compensation System and Performance Allowances Within the National Police - Sasongko, Moch. Angga Bagus; Soeling, Pantius Drahen (GoAcademica Research & Publishing, 2023)
The application of the principle of justice in providing compensation in the National Police is an interesting thing to discuss. With the enactment of the new ASN Law, which in detail explains the rights of civil servants and PPPK to support the transformation of employee welfare, of course, this is a challenge for the National Police in promoting a better compensation system that implements and prioritizes the Principle of Justice. With this method, it is expected to provide a comprehensive and comprehensive picture related to the system of providing compensation and performance allowances within the National Police. The results showed that remuneration was considered unable to appreciate the expertise of members in carrying out their daily duties. Some members with certain skills, that other members do not have, are not distinguished, so they are given the same reciprocity. In addition, in some cases, the calculation of remuneration is more emphasized on administrative aspects, such as absenteeism, without taking into account more deeply the performance and achievements carried out by each personnel every day The National Police is expected to have strategic steps in optimizing the compensation system for all its personnel, by paying attention to and evaluating the compensation system both in the form of improving the performance management system and evaluation of existing positions in the National Police agency. This is certainly a positive step in reforming the compensation system that has been imposed by the National Police.